Investigating Optimal EEG Channels and Features for Brain-Computer Interfaces: An Exploration using Evolutionary Algorithms and Machine Learning - Ali Ekhlasi; Hessam Ahmadi; Mohammad Saleh Hoseinzadeh (Frontiers in Biomedical Technologies)
Purpose: Brain-Computer Interfaces (BCI) are advanced systems that enable a direct neural pathway between the human brain and external devices. The importance of BCI is underscored by its profound implications for medical therapeutics, particularly in neurorehabilitation.